Italian (ACME, 2020)
The essay analyzes the motivations that led the musician Franchino Gaffurio to postpone the publication of his work De harmonia musicorum instrumentorum opus, published in 1518 in Milan, due to the events that led to the fall of the Sforza dynasty and the consequent French domination of the duchy of Milan. A miniature on paper 5 of the homage copy sets in the Biblioteca Comunale Laudense (manuscript XXVIII A 9), allowed to identify the second dedicatee of the text in Bonifacio Simonetta, Cistercian abbot of Santo Stefano al Corno whose face, however, was abraded due to the political struggle between Citeaux and the reformed Lombard houses, forcing Gaffurio to identify a new financier, to be found in the ranks of the numerous French gentlemen who played a leading role in the management of the State, deeply reformed by Louis XII, king of France.